Hubungan Adversity Quotient (AQ) dan Kemampuan Komunikasi Matematis Peserta Didik pada Materi Statistika - Mas Arifin Rasdhakim; Ade Mirza; Dona Fitriawan; Mohamad Rif’at; Rustam (Kilau Publishing, 2026)
This study aimed to describe students’ mathematical communication ability and adversity quotient (AQ) and to examine the relationship between the two variables in statistics. A quantitative approach with a correlational design was employed. The population consisted of 348 eleventh-grade students at SMA Negeri 5 Pontianak in the 2025/2026 academic year. Using cluster random sampling, Class XI-H, comprising 34 students, was selected as the research sample. Data were collected through a mathematical communication ability test and an AQ questionnaire. Descriptive statistics and Pearson product-moment correlation were used to analyse the data after the ordinal AQ scores were transformed into interval data using the Method of Successive Intervals. The results showed that the students’ mean mathematical communication ability was 62.27%. The achievement percentages for mathematical expression, drawing, and written text were 79.17%, 58.82%, and 48.82%, respectively. Seven students were classified in the high category, seven in the moderate category, ten in the low category, and ten in the very low category. The mean AQ score was 83.26, with 18 students classified as campers and 16 as climbers; no students were classified as quitters. The correlation analysis yielded a coefficient of (r = 0.217), which was lower than the critical value of (r = 0.339). These findings indicate a positive but weak and statistically non-significant relationship between AQ and students’ mathematical communication ability. Therefore, students’ AQ was not significantly associated with their mathematical communication ability in statistics.